Peranan Penting One Hour Notice Bagi Kru Dek di MT. Gas Soechi XXVIII - Bryan Felix Gabriel Katili; Hadi Setiawan; Frisca Mareyta Pongoh (KALAO'S MARITIME JOURNAL, 2024)
Ignorance of information is a very fatal matter. Many incidents occur due to the lack of information resulting in the absence of preparation. In the maritime world, sailors are certainly familiar with the term One Hour Notice (OHN), which is a notice or announcement one hour before the ship departs, arrives, or undergoes relocation.The type of research used in this study is qualitative research, by examining and analyzing the results of observations, as well as conducting interviews about the important role of One Hour Notice (OHN), and how to implement One Hour Notice (OHN) procedures for deck crew on MT. GAS SOECHI XXVIII. The results obtained from the research on MT. GAS SOECHI XXVIII are: (1) Understanding the importance of One Hour Notice (OHN) when the ship is about to depart, arrive, or undergo relocation, (2) Procedures for implementing One Hour Notice (OHN) for deck crew.